3-Phenyllactic acid generated in medicinal plant extracts fermented with plant-derived lactic acid bacteria inhibits the biofilm synthesis of Aggregatibacter actinomycetemcomitans - Shakya, Shrijana; Danshiitsoodol, Narandalai; Noda, Masafumi; Inoue, Yusuke; Sugiyama, Masanori (Frontiers in Microbiology, 2022)
In the present study, the effect of PLA on a periodontic pathogen, Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), the biofilm, and virulence-related genes was investigated. We confirmed that two lactic acid bacteria (LAB) strains isolated from plant sources, Lactiplantibacillus plantarum MSC-C2 and Pediococcus pentosaceus K40, secrete PLA into the de Man, Rogosa & Sharpe (MRS) broth when supplemented with phenyl pyruvic acid (PPA) as a precursor to PLA. Moreover, PLA was generated in the fermentation broths of two medicinal plant extracts, Paeonia lactiflora Pall (PR) and Carthamus tinctorius (CT), when used by each LAB strain and each extract supplemented with PPA. We determined that the minimum inhibitory concentration (MIC) of PLA against A. actinomycetemcomitans was 20 mM. PLA significantly decreased biofilm formation and suppressed the transcription of pgA, ltxA, and cdtB genes, which encode the poly-N-acetylglucosamine (PGA) polysaccharide of biofilm matrix and exotoxins leukotoxin and cytolethal distending toxin (CDT), respectively. The PLA produced by the MSC-C2 and K40 strains was increased several times by the addition of PPA to the MRS broth. The anti-biofilm effect of the extracts from the fermentation broth was proportional to the increasing PLA concentration, while a cumulatively higher effect than that of PLA alone suggested a combinational effect of PLA and the other metabolites, such as lactic acid (LA). Among the two medicinal plants, PLA, produced after the addition of PPA, was higher in PR extract incase of both the LAB strains. PLA production by the MSC-C2 strain in the PR extract reached 4.8 ± 0.23 mM, which was obviously higher than that in the MRS broth (3.88 ± 0.12 mM) supplemented with 1 mg/ml PPA. The activity to inhibit biofilm formation in the fermented PR extract was clearly high. PLA formed in the fermented PR extract downregulated the dispersin B encoding the dspB gene together with pgA, ltxA, and cdtB. In conclusion, this study shows a promising activity of PLA against the A. actinomycetemcomitans biofilm and virulence genes. In addition, the combinational effect of PLA and the medicinal plant extract can be achieved by fermentation with a specific plant-derived LAB strain.